(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Tracheal extubation is a critical phase of general anaesthesia during which patients may experience discomfort or partial awareness. Although intraoperative awareness has been widely studied, recall of discomfort during extubation remains underexplored. Aim: This study aimed to estimate the proportion of patients who recall discomfort during tracheal extubation and to evaluate its characteristics. Methods: This prospective observational study was conducted in a tertiary care hospital and included 308 adult patients (ASA I–II) undergoing elective surgeries under general anaesthesia. Standard anaesthetic protocols were followed for all patients. Postoperatively, patients were interviewed using a structured questionnaire to assess recall of extubation, presence of discomfort, type, intensity (Numeric Rating Scale, NRS), and duration of symptoms. Data were analyzed using descriptive statistics. Results: Out of 308 patients, 10 (3.2%) reported recall of the extubation process, while 298 (96.8%) had no memory of the event. Discomfort during extubation was reported by 4 patients (1.3%), whereas 304 (98.7%) experienced no discomfort. Among those with discomfort, the most common symptom was sore throat (50%), followed by coughing (25%) and choking or breathing difficulty (25%). The intensity of discomfort was mild (NRS 1–3) in all patients (100%), with no cases of moderate or severe discomfort. The duration of symptoms was less than 5 minutes in all cases (100%), indicating transient and self-limiting discomfort. Conclusion: Recall of discomfort during tracheal extubation is rare (1.3%) and, when present, is typically mild and short-lived. Standard anaesthetic practices appear effective in minimizing both awareness and distress during extubation. These findings provide reassurance regarding patient comfort and support the safety of routine extubation techniques.